Population Pressure on Agricultural Land due to Land Conversion in the Suburbs of Yogyakarta. Issue 1 (1st September 2022) - Ariani, R D; Susilo, B
Abstract: The agricultural sector is one of the sectors that has a multiplier effect on others in which ultimelty affects the regional economy. The uncontrolled development of urban areas will threaten the existence of the agricultural sector due to the conversion of agricultural land into built-up areas and trigger an acceleration of migration which results in high population growth rates. The increasing rate of population growth will also increase the need for land for settlements, industry or services which leads to population pressure on agricultural land so that it affects the carrying capacity of the land. This study aimed to determine the level of population pressure on agricultural land and the level of carrying capacity of agricultural land on the suburbs of Yogyakarta City. The method used in this research was descriptive quantitative with the research location was on the suburbs of Yogyakarta and the main data source was secondary data. Population pressure on agricultural land was analyzed using the Otto Soemarwoto Model I formula which is presented in the form of tables and maps. The results of the analysis showed that population pressure on agricultural land on the suburbs of Yogyakarta exceeded the threshold (TP>1). Meanwhile, the carrying capacity of the land was very low in which the area was no longer able to carry out food self-sufficiency to meet the food needs of the population (α<1). Efforts that can be done to increase the carrying capacity of agricultural land are conservation, prevention and rehabilitation of agricultural resources.